Endogenous development potential and local development strategies in the municipal development plans of Aburrá Sur 2016-2019. - Toro López, Daniela
The endogenous potential of a territory represents the set of resources of different nature, which can be exploited in order to constitute a sustainable and competitive development. Its analysis has constituted, in turn, the endogenous development theory that explains how territories develop from their own resources. Particularly the Aburrá Sur, a conurbation in Antioquia-Colombia, is an important geoeconomic zone of the country due to its high rate of development in the productive sector. The objective of this research was to analyze the inventory of endogenous potential resources of Aburrá Sur and their relationship with the local development strategies contained in the municipal development plans 2016-2019. It was conducted through a case study with a mixed methodology evaluating the endogenous development potential and the municipal development plans of the municipalities of Aburrá Sur and contrasted with the results of a survey implemented during 2020 to entrepreneurs in the territory. The results show that the actions have been positive and that many of the goals proposed in the development plans have been achieved in accordance with the economic resources allocated. In addition, the institutional component is suggested as one of the main factors in the development of this region.